Moderately elevated erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP) in patients with no clinical signs or symptoms of infection is not a contraindication for total knee arthroplasty: a retrospective cohort study. Issue 1 (12th January 2022) - Yeganeh, Ali; Amiri, Shayan; Moghtadaei, Mehdi; Otoukesh, Babak; Solati, Ahmadreza; Daneshmand, Seyedehsan
Abstract : Background: It is unclear whether patients with elevated preoperative levels of erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP) are more prone to periprosthetic joint infection (PJI) after total knee arthroplasty (TKA). The authors aimed to determine how preoperative moderate elevation of ESR or CRP in patients without clinical signs or symptoms of infection is associated with the risk of PJI after TKA surgery. Methods: In a prospective study, 315 patients who were elected for unilateral TKA were included, including 237 patients with preoperative normal ESR and CRP, 46 patients with moderate preoperative elevation of ESR (less than 50 mm/hr), and 32 patients with moderate preoperative elevation of CRP (less than 24 mg/dL). Patients with both ESR and CRP elevation were not included in the study. Primary TKA was done using a standard medial parapatellar approach under general anesthesia. Results: Overall rate of infection was 0.3% (1 in 320 patients) at a mean follow-up period of 19±5.3 mo. This infection occurred in a patient with normal preoperative ESR and CRP (1 in 237 patients, 0.4%). No infection occurred in 78 patients in either the ESR-elevated or the CRP-elevated group. Accordingly, the rate of infection was not significantly different between the two groups ( P =0.83). Conclusions: Moderate preoperative elevations of ESR or CRP do not increase the rate of periprosthetic joint infection in patients undergoing total knee arthroplasty. Level of Evidence: Level III.